HUBUNGAN KONSUMSI JAJANAN KARIOGENIK DENGAN KARIES GIGI PADA MURID KELAS IV DAN V SEKOLAH DASAR NEGERI 2 CEMPAKA KOTA BANJARBARU - Yanti, Maulida; Salamah, Siti; Said, Fahmi (Poltekkes Kemenkes Banjarmasin, 2022)
Elementary school is 2 cempaka one of two elementary schools located suburban Banjarbaru based on and random checks for class I to VI respectively 2 people, who totaled 12 people. 10 of them had dental caries. The purpose of this study was to determine the relationship of cariogenic snack consumtion with dental caries in fourth and fifthgrade student in elementary school 2 Cempaka Banjarbaru City. Based on the results of the study were 32 respondent or 50.8% in the habit of eating snacks carieogenic often, with number of dental caries, 40 respondent or 63.5%, while as many as 31 respondent (49.2 %) in the habit of rarely consumed cariogenic snack with numbers its low caries by 23 respondents or 36,5 %. Significan value (sig) = 0.000 and the value of alpha = 0.005 which sig<alpha (0,000< 0.005), so Ho is rejected and Ha accepted that there is a relationship between the consumption of cariogenic snacks with dental caries in fourth and fifth grade student of SDN 2 Cempaka City Banjarbaru. For dental health workers ought to maximize at puskesmas UKGS activities in order to caries can be prevented and caught early, and perform dental fillings, cavities that process does not continue, constantly improve and provide knowledge on the impac of cariogenic snacks consumed in large quantities, without regard to hygiene and health teeth and mouth and give firmness to the merchants that do not sell food that could damage the health of the teeth aroud the school, so that school snack habit can be reduced